En bloc GreenLight laser enucleation of the prostate (GreenLEP): An in‐depth look at the anatomical endoscopic enucleation of the prostate using a 532‐nm lithium triborate laser. (14th July 2020) - Rijo, Enrique; Misrai, Vincent
Abstract: GreenLight laser enucleation of the prostate (GreenLEP) is an alternative endoscopic enucleation of the prostate (EEP) technique for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostatic obstruction (BPO). GreenLEP is an 'en bloc' EEP technique to remove the transitional zone tissue in one piece. The procedure is a combination of laser enucleation and blunt gentle mechanical dissection using the tip of the resectoscope. The advantage of mechanical dissection is that it allows for better visualisation of the capsule and in some cases makes the dissection a little faster. This procedure is performed with a 532‐nm lithium triborate laser (GreenLight™ XPS 180 W generator, AMS), a 2090 side‐firing fibre and a Piranha™ morcellator (Richard Wolf GmbH). We offer a review of the evolution of the technique including the most important technical aspects, complications, advantages/disadvantages, tips and tricks and a visual step by step guide to perform the GreenLEP technique. GreenLEP is one of the latest energy sources reported in the armamentarium of EEP techniques for the treatment of BPO. GreenLEP has previously demonstrated its feasibility, safety and similar short‐ to mid‐term functional outcomes compared to surgical gold standards in the literature.